A Regarded Self : Caribbean Womanhood and the Ethics of Disorderly Being - Glover, Kaiama L., 1972- (Book collections on Project MUSE., 2021)
"Kaiama L. Glover examines Francophone and Anglophone Caribbean literature whose female protagonists enact practices of freedom that privilege the self, challenge the prioritization of the community over the individual, and refuse masculinist discourses of postcolonial nation building"--